PENGARUH PEMANGKASAN TERHADAP PRODUKSI TUNAS PADA KEBUN PANGKAS BIDARA LAUT (Strychnos lucida R Brown) [The Effect of Hedging to The Production of Shoots on The Hedge Orchard of Strychnos lucida R Brown] - Krisnawati Krisnawati; Anita Apriliani Dwi Rahayu (Journal Penelitian Kehutanan FALOAK, 2017)
ABSTRACT  Bidara laut (Strychnos lucida R Brown) is a potential of traditional medicinal plant, especially in the area of Bali and NTB. Efficacy of S. lucida wood is used to malaria medicine and stamina enhancer. One way to ensure the supply of raw material of S. lucida, need to be cultivated as plant propagation by cuttings. Vegetative propagation of plants using shoot cuttings needs juvenile plant material. One of way to get it is build the hedge orchard. Hedging techniques are necessary aspect on hedge orchard management whose role is to determine the productivity and quality of the cutting materials. This study aims to determine the effect of stock plant height after hedging (10 cm and 20 cm) to the production of shoots. The study design used completely randomized design. The parameters measured were the number of shoots and length of shoot after four months of observation. The results showed that the difference of stock plant height of S. lucida after hedging affects the number of shoots and length of shoots that was produced. Average of number of shoots that was produced after four months on height of hedging at 20 cm was higher than height of hedging at 10 cm i.e. 2.59 shoots. This was contrasts with an average of length of shoots which produced that height of hedging at 10 cm would indicate that the length of shoots was better than at 20 cm i.e. 8.99 cm.                                                         ABSTRAKBidara laut (Strychnos lucida R Brown) merupakan tumbuhan obat tradisional yang potensial, khususnya di wilayah Bali dan NTB. Khasiat kayu bidara laut antara lain digunakan sebagai obat malaria dan penambah stamina. Salah satu cara untuk menjamin pasokan bahan baku kayu bidara laut, perlu dilakukan budidaya seperti perbanyakan tanaman dengan stek. Perbanyakan tanaman secara vegetatif menggunakan stek pucuk memerlukan bahan tanaman yang juvenil. Salah satu cara untuk mendapatkannya yaitu dengan membangun kebun pangkas. Teknik pemangkasan merupakan aspek yang diperlukan dalam pengelolaan kebun pangkas yang berperan untuk menentukan produktivitas dan kualitas bahan stek. Penelitian ini bertujuan untuk mengetahui pengaruh tinggi tanaman induk setelah pemangkasan (10 cm dan 20 cm) terhadap produksi tunas. Rancangan penelitian menggunakan Rancangan Acak Lengkap. Parameter yang diukur adalah jumlah tunas dan panjang tunas setelah 4 bulan pengamatan. Hasil penelitian menunjukkan bahwa perbedaan tinggi tanaman induk bidara laut setelah pemangkasan mempengaruhi jumlah tunas dan panjang tunas yang dihasilkan. Jumlah tunas rata-rata yang dihasilkan setelah 4 bulan pemangkasan pada tinggi pangkasan 20 cm lebih baik dibandingkan tinggi pangkasan 10 cm yaitu 2,59 tunas. Hal ini berkebalikan dengan panjang tunas rata-rata yang dihasilkan, tinggi pangkasan 10 cm justru menunjukkan panjang tunas yang lebih baik dibandingkan tinggi pangkasan 20 cm yaitu 8,99 cm.